Pendampingan STBM Dalam Bidang CTPS Di SD Negeri 1, 2, dan 3 Bantas Kecamatan Selemadeg Timur Tahun 2018 - Ni Ketut Rusminingsih; I Nyoman Purna; I Nyoman Sujaya; M. Choirul Hadi; Wayan Jana (Poltekkes Kemenkes Denpasar, 2019)
Community-Based Total Sanitation (STBM) is an approach to change hygiene and sanitation behavior through community empowerment through triggering methods. CTPS is one of the 5 pillars of STBM which focuses on the availability of washing hand facilities (water, soap, hand washing facilities) in the community including schools. This activity needs to be accompanied because it has not been entrenched in the community service location. The purpose of this community Hands and a positive increase in knowledge and behavior after being given counseling about washing hand behavior with soap. Suggestion: So that the school principal and the teachers routinely provide socialization to their students about the importance of washing hands with soap and supervision of the cleanliness of the sink that was built. Assistance, construction of sinks and washing hands with swap service is to increase understanding of elementary school students regarding the behavior of washing hands with soap with a method of assistance with the construction of facilities for washing hands, counseling and screening of films on handwashing with soap. The target of this activity is elementary school students from grade 1 to grade 6 with the implementation time in September 2018 at SD Bantas 3, Selemadeg Timur District in 2018. Results: there is an increase in positive knowledge and behavior about the behavior of washing hands with soap in elementary school children 3 Bantas through assistance. Conclusion: making 2 washing hand places and a positive increase in knowledge.Keywords: Assistance, washtafel build and washing hand with soap